Rekruitmen Politik Caleg Partai Gerindra di DPRD Provinsi Sumatera Barat pada Pemilu 2019 - Permata Sari, Yustika; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2023)
This study aims to determine how the recruitment process of Gerindra Party candidates in West Sumatra Province. The research method used is quasi qualitative research. The types and sources of data used in this study are primary data and secondary data. The data validity test of this research uses source triangulation techniques. In this study, data analysis techniques were carried out with three flows, namely data reduction, data presentation and conclusion drawing. The research uses the theory of Pippa Norris' candidate recruitment stage with the results of this study, namely: 1) The Certification Stage is a screening stage where the Gerindra Party conducts as much screening as possible in various circles without limiting anyone who wants to register to become a candidate with a note that of course they must meet the requirements, 2) The Nomination Stage is a screening stage where the Gerindra Party screens or verifies the files of prospective candidates who have registered in the context of selecting prospective candidates for the Gerindra Party of West Sumatera Province for the 2019 Election and 3) The Selection Stage is a stage where a list of candidates who have been nominated to then continue a series of candidate selection processes in the form of assessment tests consisting of written tests and interview tests. Meanwhile, the supporting factors that influence the victory of candidates in increasing representation in the West Sumatera Provincial DPRD are: 1) Prabowo-Sandi effect, 2) Incumbent Legislative Candidates.